(3YLGFH GdebOhQ aj fhGFH JjehQs - (3CMeO Hf eMeO Hf YHO Gddg Hf EHQGgje, CHh eMeO, TgGH GdOjf, GdeYQha HGHf nYnQrHTGg , J (B854 (3g` s ((3eMeO GdHQdSj s)
(3ChdgG (B:s
(3hCbSe dGjHQM Yf GdebGheI hdGjQLY aj eLdS bVGA GdMQH Yf edGReI GdeUGOeI s
(3BNQgG (B:s
(3hGdeSFhd ef UObGJ Phi GdCOH Cf jSHdhG Pjd GdEZVGA Ydjg s
(3GfXQ Qbe (B329s
(3Qbe (B735 (3JGQjNs
(3fSNI KGdKI HQSe GdCejQ YdhGf MdHjs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs